2016
DOI: 10.1016/j.cell.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reconstitution Reverses Maternal Diet-Induced Social and Synaptic Deficits in Offspring

Abstract: SUMMARY Maternal obesity during pregnancy has been associated with increased risk of neurodevelopmental disorders, including autism spectrum disorder (ASD), in offspring. Here we report that maternal high fat diet (MHFD) induces a shift in microbial ecology that negatively impacts offspring social behavior. Social deficits and gut microbiota dysbiosis in MHFD offspring are prevented by co-housing with offspring of mothers on a regular diet (MRD) and transferable to germ-free mice. In addition, social interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
924
7
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 933 publications
(978 citation statements)
references
References 56 publications
41
924
7
6
Order By: Relevance
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
See 2 more Smart Citations
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…Like humans, rodents are naturally social animals, but GF rats and mice exhibit deficits in social behaviors such that they show less interest in social interaction and poorer memory for social partners. [89,[110][111][112] Deficits in social behavior are also observed following antibiotic-induced depletion of the microbiota. [72,113] The microbiota also plays a role in murine models of ASD, where treatment with specific bacteria has been shown to reverse many of the social deficits observed in these animals.…”
Section: Microbiota Is Critical For Social Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The results supported the gut-microbiome-brain connection in the mouse model of ASD and identified a potential therapeutic target. Another recent report also indicated that maternal high-fat diet could induce a shift in gut microbial ecology and negatively impact offspring's ASD-like social behavior [25]. Clinical case study also observed reduced severity of abdominal symptoms and improvement of ASD core symptoms after a multi-strain mixture of ten probiotics treatment for 4 weeks and followed by a four month followup observation on a 12 year old boy with ASD and severe cognitive disabilities [26].…”
mentioning
confidence: 76%
“…Third, these data point to a new gut-brain signaling axis in controlling the development of inflammatory and degenerative pathology in humans. These findings also add to recent advancements made in studies of neuropsychiatric disease where the gut microbiota modulate transcriptional programs that control social behavior (92), modulate synaptic dysfunction (93), and can modulate phenotypes associated with autism (94). It should also be kept in mind that, besides acting as a CNS sensor for immunomodulatory metabolites produced in the gut, based on its effects on gut immunity AhR may also shape the gut flora, impacting the gut-brain axis at multiple levels.…”
Section: Role Of Ahr In Astrocyte-mediated Inflammatory Processesmentioning
confidence: 99%